Influence of white etching layer on rolling contact behavior at wheel-rail interface - Qinglin Lian (Friction, 2020)
Abstract The existence of narrow and brittle white etching layers (WELs) on the rail surface is often linked with the formation of rail defects such as squats and studs, which play the key roles in rail surface degradation and tribological performance. In the present study, a systematic investigation on stress/strain distribution and fatigue life of the WEL during wheel-rail rolling contact was conducted based on a numerical model considering the realistic wheel geometry. This is the first study considering the influence of rail materials, loading pressure, frictional condition, WEL geometry (a/b), and slip ratio (Sr) in the practical service conditions at the same time. The results revealed much higher residual stress in WEL than in rail matrix. Stress changes along the rail depth matched with the previously reported microstructure evolutions. The current work revealed that the maximum difference in contact stress between the wheel passages of rail matrix and the WEL region (noted as stress variation) rises with the increase of loading pressure, the value of a/b, and Sr; but drops with the friction coefficient (μ). In addition, a critical length-depth ratio of 5 for a/b has been found. The fatigue parameter, FP, of the WEL decreased quickly with the length-depth ratio when it was less than 5 and then increased slightly when it was larger than 5. This study also revealed that the fatigue life of the WEL was reduced for high strength head hardened (HH) rail compared with standard carbon (SC) rail.